The magnificent makers. Trash and treasure - Humeniuk, Ben (PowerKids Press, 2020)
Sadie learns of a maker competition and she sees it as her chance to finally beat a rival school. She takes control of her group, who quickly feel bullied. Then Sadie's project is sabotaged, but she learns the real culprit might be a member of her own team.